Efficacy of Enzotein in post-operative recovery and morbidity reduction in acute necrotizing pancreatitis: a case report - Rodrigues, Frazer C. S.; Rodrigues, Jude; Amonkar, Amol; Talaulikar, Samiksha Shyam Naik; Kumar, Saurav (International Journal of Basic & Clinical Pharmacology, 2024)
Acute pancreatitis (AP) is a clinical syndrome defined by a discrete episode of abdominal pain and elevations in serum enzyme levels. A 40-year-old male driver from a lower socioeconomic background presented with epigastric and umbilical pain, weighing 60 kg and measuring 157 cm. A detailed case history followed by investigations confirmed acute necrotizing pancreatitis with fluid collection. Management involved a Malecot catheter insertion, draining fluid with high amylase. Follow-up showed increasing fluid collection, necessitating necrosectomy, NJ tube insertion, and laparostomy after seven weeks. Post-surgery, recovery involved dressings, physiotherapy, and a high-protein diet with Proteinace 98. By two years, the patient achieved 75 kg weight, BMI 24 kg/m², improved muscle mass, controlled diabetes and hypertension, alcohol abstinence for three years and had resumed his work.